Service Level of Pharmaceutical Supply Chain Applying Optimal Policy: Case Study in Lima, Perú - Kevin Arana; Katherine Flores; Edgar D. Ramos; Timothy Pettit; Monica Flanigan (International Journal of Supply Chain Management, 2020)
Low service level is a serious problem for distribution companies in the pharmaceutical sector of Peru, mainly due to the uncertainties in the supply chain, coming from suppliers and customers. An important contributing factor is the inadequate management of inventories, since they do not know in advance the amount and right moment to place the order, thus generating a negative economic impact. Faced with this scenario, the proposal of this study is based on the development of an optimal supply policy for the sector considering two echelons (distributor and retailer), with the aim of increasing the service level and, therefore, the performance of the supply chain. The proposed method was solved analytically, and the solution has been illustrated with data obtained from an enterprise in the pharmaceutical sector using a sensitivity analysis; in turn, it was observed that as the service level increases, a greater total profit of the chain is obtained